Malaysia Madani Concept: An Exploration of Its Islamic Dimensions and Characteristics - Ushama, Thameem (Advances in Social Sciences Research Journal, 2025)
This paper explores the Malaysia MADANI concept, represented by the Malay acronym for “SCRIPT,” which stands for keMampanan (Sustainability), kesejAhteraan (Prosperity), Dayacipta (Innovation), hormAt (Respect), keyakiNan (Trust), and Ihsan (Care and Compassion). The concept has been criticised by academics, leaders, scholars, politicians, students, and the public. The primary aim of this study is to understand the essence of the MADANI concept and to clarify it in light of the Tawhidic epistemology and the Islamic worldview. Given the limited attention paid to MADANI, this paper examines its features and dimensions within the context of the Qur’ān, Sunnah, and Islamic heritage. A qualitative methodology, focusing on content analysis, has been employed. Selected exegeses of the Qur’ān and narrations from Ḥadīth literature, alongside the thoughts of Muslim scholars, have been reviewed to elucidate the concept and demonstrate its significance for a proper understanding of MADANI. The study begins with an introduction, followed by a brief overview of selected Muslim scholars’ perspectives on good governance, along with a discussion of the study’s problem, methodology, and objectives. It then presents the Arabic terms associated with the six drivers of MADANI, along with their scriptural sources. The study addresses key concepts, including sustainability, care, and compassion, as essential elements for harmony; respect as the foundation of an inclusive community; innovation as a model for sustainable development; prosperity as a crucial driver of societal advancement; and trust as a pathway to holistic well-being, from an Islamic perspective. The paper concludes with recommendations based on the findings.